PENGARUH PENERAPAN MODEL PEMBELAJARAN CARD SORT TERHADAP KETERAMPILAN MENULIS SYAIR SISWA KELAS VII C SMP NEGERI 5 KOTA JAMBI TAHUN AJARAN 2017/2018 - Abdoel Gafar; Devila Ulfa (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this research is to describe the card sort learning model towards students class VII C writing skill at SMP Negeri 5 Kota Jambi. This research is Quasi eksperiment by using quantitative approach. This research used 1 experimental class which consists of 36 students by using Liliefors test. The requirement test used in this research is normality and homogeinity test. The result of normality pre-test  is -92,48 and post-tes is -432 and the homogeinity score is 0,57 which is higher than significant = 0,05. It means that the data is normal and homogen so that hypothesis test can be tested. Hypothesis test is done by using t test formula. The result shows that the score of  is 1,859 which is higher that the score of  1,000 with significant  = 0,05 with dk 36. It can be concluded that there is a significant correlation between the use of Card sort learning model towards students class VII C writing skill at SMP Negeri 5 Kota Jambi in which the mean category is 93,33 more higher than the mean of pre-test 76,80 Keywords:  The Effect, Card Sort, Poetry Writing